2010
DOI: 10.1016/j.neuropsychologia.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic medication boosts action–effect binding in Parkinson's disease

Abstract: Abstract:Parkinson's disease (PD) is a neurodegenerative disorder affecting voluntary motor control. shift towards the preceding action that caused the tone, relative to a baseline condition involving tones only. The patients were tested both on and off dopaminergic medication. PD patients off medication showed no significant change in action-effect binding relative to controls. Conversely, PD patients on medication showed a significant increase in actioneffect binding relative to their own performance off med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 60 publications
(41 reference statements)
6
90
0
1
Order By: Relevance
“…Here, it is harder to rule out remote effects. One recent study showed intact intentional binding in patients with Parkinson's disease (Moore et al 2010). BG dysfunction in Parkinson's disease, and putative disruption of BG function by remote effects of cTBS over pre-SMA, are clearly not strictly equivalent.…”
Section: (A) Limitationsmentioning
confidence: 99%
“…Here, it is harder to rule out remote effects. One recent study showed intact intentional binding in patients with Parkinson's disease (Moore et al 2010). BG dysfunction in Parkinson's disease, and putative disruption of BG function by remote effects of cTBS over pre-SMA, are clearly not strictly equivalent.…”
Section: (A) Limitationsmentioning
confidence: 99%
“…The errors were calculated by the difference between perceived and actual moments of time. Following this, the intentional binding is calculated through the formulas shown in Figure 3 [46]. As shown in Figure 3, in baseline conditions participants perceived the action earlier but the outcome later when compared to the actual time.…”
Section: The Intentional Binding Paradigmmentioning
confidence: 99%
“…The principal measures include binding of action (the delay in the perception of action and its attraction towards the time of tone) and binding of tone (the earlier perception of tone and its attraction towards the time of action) (Haggard et al, 2002). One can also examine “composite” binding, in terms of the sum of action binding and tone binding (Moore et al, 2010b; Moore and Obhi, 2012), although there are caveats to this approach (see below).…”
Section: Intentional Binding: Objective Chronometry In the Study Of Amentioning
confidence: 99%